2021
DOI: 10.1103/physrevlett.126.117003
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Synthesis of Yttrium Superhydride Superconductor with a Transition Temperature up to 262 K by Catalytic Hydrogenation at High Pressures

Abstract: The recent observation of room-temperature superconductivity will undoubtedly lead to a surge in the discovery of new, dense, hydrogen-rich materials. The rare earth metal superhydrides are predicted to have very high-Tc superconductivity that is tunable with changes in stoichiometry or doping. Here we report the synthesis of a yttrium superhydride that exhibits superconductivity at a critical temperature of 262 K at 182 ± 8 GPa. A palladium thin film assists the synthesis by protecting the sputtered yttrium f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
163
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 228 publications
(180 citation statements)
references
References 37 publications
(49 reference statements)
6
163
0
Order By: Relevance
“…Here, we also discuss the contradictions between different experimental data for the yttrium-hydrogen system. Our preliminary report 25 and the present more comprehensive data are in good agreement with the data from Troyan et al 26 but evidently contradict the claim of T c = 262 K at 182 GPa reported by Snider et al 27 .…”
Section: Introductionsupporting
confidence: 82%
See 4 more Smart Citations
“…Here, we also discuss the contradictions between different experimental data for the yttrium-hydrogen system. Our preliminary report 25 and the present more comprehensive data are in good agreement with the data from Troyan et al 26 but evidently contradict the claim of T c = 262 K at 182 GPa reported by Snider et al 27 .…”
Section: Introductionsupporting
confidence: 82%
“…5 ). This strong disagreement raises a question about the material studied in Snider et al 27 . Unfortunately, the lack of any X-ray structural characterisation of the samples in Snider et al 27 makes the direct comparison impossible.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations